Association of anatomic variations with antrochoanal polyps in paranasal sinus computed tomography scan - Hekmatnia, Ali (J Res Med Sci, 2017)
BACKGROUND: This study was designed to determine the prevalence of concomitant anatomic variation of paranasal sinuses in patients with antrochoanal polyp (ACP). MATERIALS AND METHODS: Among patients referred by their clinicians for standard computed tomography scan of paranasal sinuses septal deviation, concha bullosa, and retention cyst were evaluated in both patients with ACP as well as in a control group. RESULTS: Of the 17 patients with ACP, fifteen patients (88.2%) had septal deviation and two patients (11.8%) had concha bullosa. None of the patients with ACP had retention cyst or hypertrophic turbinate. Of the 78 patients in control group, twenty-nine (37.2%) had septal deviation, six (7.7%) had concha bullosa, seven (8.9%) had retention cyst, and one (1.2%) had hypertrophic turbinate. Septal deviation in patients with ACP has higher incidence (P < 0.001). CONCLUSION: This study showed that septal deviation is an anatomic variation which is significantly concomitant with ACP. Larger studies are needed to show the role of other anatomic variations in patients with ACP.